What's Different about Bank Holding Companies? - Chami, Ralph (IMF Working Papers; Working Paper ;, 2017)
The recent fnancial crisis highlighted the role of Bank Holding Companies (BHCs) in exacerbating the crisis and in transmitting monetary policy beyond the local economy to global markets. Yet, little is known about their behavior, as most models of banking typically focus on banks with a loan desk. We develop a dynamic model of a BHC that encompasses both a trading desk and a loan desk, and explore the role of risk attitude and overleveraging by the trading desk. We trace the impact of monetary policy and market innovations on bank behavior in the presence of Basel III type regulations. To our knowledge, this is a first such exercise. We show that the value of the BHC is enhanced by operating both desks, even if they both are subject to common market shocks. We explore alternative regulatory remedies to ongoing efforts to ring-fence the proprietary trading business, and show that regulations that target bank governance can mitigate possible rogue trading and the overleveraging problem.